Managing scientific knowledge on the internet for students' needs - Bogdanović Miloš; Žikić Olivera (Trendovi u Poslovanju)
As a supermedium used for communication by today's generations, the Internet offers huge advantages to its users in comparison with older media: immesurably more open access to information, the freedom to choose the source of information and content itself, as well as the possibility to create one's own content and emit it towards other users. Likewise, English has become a super language and its knowledge a necessity in the Internet knowledge management. The aim of this paper is to help students recognise scientific knowledge while browsing the Internet, as well as how to organize that knowledge and their ideas in the best possible way, when deciding to be researchers. Which online sources are reliable and which ones are not? Although there is a clear cut classification which university websites are more reliable than e.g. pop-science websites, social networks are a useful alternative as a source of accurate and valuable information and knowledge. How does one efficiently find scientific information and manage the cumulative amount of documents and data? A useful skill which makes the use of the Internet for educational and research purposes easier is advanced use of Google operators. We will also demonstrate how some applications for better work organization and productivity (Evernote, Dropbox, Mendeley) could be used for the purpose of managing scientific knowledge.